RESEARCH AND EDUCATION PRIORITIES IN THE DEVELOPMENT OF SOUTHERN FEDERAL UNIVERSITY - Marina S. Borovskaya (Высшее образование в России)
Southern Federal University became one of the universities of a new type - research universities, which answer the requirements of the global world and the trends of the modern technical and economic development. Integration of education process with the advanced scientific research and innovation activities, R&D and institutional innovations ensured formation of intellectual and infrastructural basis for social and economic development of the country and training of specialists, which have practical skills and special competences in up-to-date technologies and able to solve creative science-junction tasks. The graduates of new federal university are expected to be such specialists of a new generation, who will form the future social and intellectual elite.